Manajemen Boarding School Sebagai Sarana Pengembangan Karakter Peserta Didik di SMAN 13 Pangkep - Ulfah Lutfyyah Syam; Herman Herman; Supriadi Torro; Nurabidah Idrus (Universitas Negeri Makassar, 2022)
This research technique was carried out by means of purposive sampling throught the following criteria: (1) school leaders (2) teachers who teach directly about character (3) boarding teachers (4) head of female dormitories. Data collection techniques were carried out through: (1) Interviews (2) Documentation (3) Observation, the data above was analyzed using the Hubermen model.The results showed that: (1) The description of Boarding School Mangement in SMA 13 can be seen in (a) Student Management (b) Teaching and Learning Process Management. (2) Boarding School’s Determinant Factors in character development are (a) Guidance Model (b) Competence of Educators/Educator’s Example (c) Emergence of student Awareness. (3) Boarding School Management’s efforts in developing the character of students are (a) Increasing discipline (b) Giving Sanctions (c) Cooperation between the school and parents.